Analisis De Longitud Telomérica En Pacientes Con Demencia Tipo Alzheimer En Colombia (2024)
Alzheimer's disease, a neurodegenerative disorder that mainly affects older people, has been linked to alterations in telomeric length, a structure that protects chromosomes. However, in Colombia, studies on telomeric length in the context of this disease are limited, since most research focuses on specific mutations. This work aimed to analyze the relationship between telomeric length and Alzheimer's disease in a sample of Colombian patients. We collected 39 peripheral blood samples from patients diagnosed with Alzheimer's disease and a control group, also evaluating factors such as age and gender of the participants. T